Use of the demographic bonus in order to undertake in unity the development of Nicaragua (Revista Multi-Ensayos, 2019)
This paper merged from the writers decision of participating in the National Contest of Essays: Youth ideas for the national development, guided by the Youth Minister (MINJUVE), in October 2018. One of the topics was the demography, specifically the demographic bonus in Nicaragua. This paper gathers a brief explanation of the importance of the topic, the definition and data about the demographic bonus in the country, also its incorporation in the governmental aspects and some ideas to use in the national development.
Keywords: development; yuth; demographic bonus; goverment of Nicaragua